2010
DOI: 10.1001/archpediatrics.2010.99
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Costs and Quality of Life During 4 Years After Very Preterm Birth

Abstract: To evaluate the effect of gestational age and prematurity-related morbidities on hospital costs and cost per quality-adjusted life-year (QALY) during the first 4 years of life.Design: Population-based study using national register data and parental questionnaires. Setting: Finland. Participants: All 2064 very preterm children (gestational age Ͻ32 weeks or birth weight Ͻ1501 g) and all 200 609 full-term control individuals (mean [SD] gestational age, 37 [0] to 41 [6] weeks) born from January 1, 2000, through De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
2
32
0
2
Order By: Relevance
“…12 This is in accordance with previous studies, which showed that the use of health care resources declines with in- creasing age in individuals who were born preterm. 13,23 Thus, the first-year hospitalization costs and, in particular, the initial hospital stay compose the great majority of the total costs of care of very preterm infants.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…12 This is in accordance with previous studies, which showed that the use of health care resources declines with in- creasing age in individuals who were born preterm. 13,23 Thus, the first-year hospitalization costs and, in particular, the initial hospital stay compose the great majority of the total costs of care of very preterm infants.…”
Section: Discussionsupporting
confidence: 93%
“…11 Our study on the total hospitalization costs during the first 4 years of life for children who were born very preterm showed similar results: the initial hospital costs composed 79% of the total costs, and thereafter the costs decreased each year. 12 In addition, individuals with prematurity-associated morbidities used significantly more hospital resources during the first 4 years of life than those without these morbidities.…”
mentioning
confidence: 99%
“…6 A recent structured review summarising published evidence on the economic consequences of LMPT birth, 6 found that ten studies, published between 1980 and 2011, focused on economic costs during the infant's initial hospitalisation, [7][8][9][10][11][12][13][14][15][16] whereas 13 studies reported economic costs in some form following the infant's initial hospitalisation. 5,7,9,13,[17][18][19][20][21][22][23][24][25] None of the latter studies estimated the economic costs of LMPT birth from a societal perspective, however, with 11 studies limited to an estimation of hospital costs, 5,7,9,13,[19][20][21][22][23][24][25] and with two limited to an estimation of health and social services or public sector costs. 17,18 Moreover, these economic studies were either based on patient cohorts, recruited over a decade ago, 5,7,9,13,17,[19][20][21]<...>…”
Section: Introductionmentioning
confidence: 99%
“…5,7,9,13,[17][18][19][20][21][22][23][24][25] None of the latter studies estimated the economic costs of LMPT birth from a societal perspective, however, with 11 studies limited to an estimation of hospital costs, 5,7,9,13,[19][20][21][22][23][24][25] and with two limited to an estimation of health and social services or public sector costs. 17,18 Moreover, these economic studies were either based on patient cohorts, recruited over a decade ago, 5,7,9,13,17,[19][20][21][22][23][24] or hypothetical cohorts simulated within models. 18, 25 The aim of this study was to estimate the economic costs during the first 2 years of life associated with LMPT birth in the context of a recent prospective population-based study.…”
Section: Introductionmentioning
confidence: 99%
“…What medical expenses are incurred after NICU discharge? That calculation depends strongly on two variables: (1) what was the infant's gestational age at birth? and (2) how much permanent morbidity remains after discharge?…”
Section: Nicu Survival and Its Costmentioning
confidence: 99%